2011
DOI: 10.1186/1297-9716-42-121
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toxoplasma gondii positivity relative to age in 125 Scottish sheep flocks; evidence of frequent acquired infection

Abstract: Toxoplasma gondii seroprevalence was determined in 3333 sheep sera from 125 distinct sheep flocks in Scotland, with the majority of flocks being represented by 27 samples, which were collected between July 2006 and August 2008. The selected farms give a representative sample of 14 400 sheep holdings identified in the Scottish Government census data from 2004. Overall T. gondii seroprevalence, at individual sheep level, was determined to be 56.6%; each flock tested, had at least a single positive animal and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 39 publications
4
39
2
1
Order By: Relevance
“…The fact that both studies also showed an increasing seroprevalence with age provides further evidence to suggest that most infections occur in the postnatal period (Hutchinson and others 2011, Katzer and others 2011). Significant regional variation in within-flock seroprevalence to T. gondii infection in sheep has also been identified in some studies.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The fact that both studies also showed an increasing seroprevalence with age provides further evidence to suggest that most infections occur in the postnatal period (Hutchinson and others 2011, Katzer and others 2011). Significant regional variation in within-flock seroprevalence to T. gondii infection in sheep has also been identified in some studies.…”
mentioning
confidence: 68%
“…For example, since the majority of samples were taken for diagnostic purposes, it is likely that flocks with a recent history of abortion will be over-represented. Furthermore, previous surveys have shown that seroprevalence in sheep tends to increase with age (Halos and others 2010, Hutchinson and others 2011, Katzer and others 2011), and although it is probable that most of the samples used in this study will have been taken from adult breeding female sheep, possible age-related effects could not be accounted for due to lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated T. gondii seroprevalences of up to 65% in small ruminants are frequently reported in the Mediterranean region and in Greece (Tzanidakis et al, 2012). In a recent study conducted in 125 Scottish sheep flocks, the overall T. gondii seroprevalence at individual level was 56.6 % (Katzer et al, 2011). In a study in France conducted in 2007, the proportion of sheep carcases carrying live parasites was 5.4 % (3-7.5 %) and molecular typing mostly revealed genotype II (Halos et al, 2010).…”
Section: Current Situation and Trends In The Eumentioning
confidence: 99%
“…Some studies have identified other husbandry practices as risk factors, such as large flock size (Klun et al, 2006;Vesco et al, 2007), use of mouse poison and non-timber construction of the sheep house (Skjerve et al, 1998), grazing sheep together with sheep from other farms (Katzer et al, 2011), and cattle kept on the same premises (Hutchinson et al, 2011), but often with large uncertainty. No evidence is available to show whether eliminating these risk factors will have any impact on the presence or prevalence of T. gondii in the flocks or herds.…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…It is considered as the most successful parasitic pathogen worldwide [1]. Although all warm blooded animals including marine mammals [2] and birds are susceptible to the infection, only felids are the definitive host of the parasite.…”
Section: Introductionmentioning
confidence: 99%